Montane plant environments in the Fynbos Biome - B. M. Campbell (Bothalia: African Biodiversity & Conservation, 1983)
Environmental data collected at 507 plots on 22 transects, and soil analytical data from 81 of these plots, have been used to describe the plant environments of the mountains in the Fynbos Biome. Two major regional gradients are recognized: a west-east gradient and a coast-interior gradient. Of particular consequence for fynbos-environment studies is the increase in the proportion of fine soil particles from west to east. At least some aspects of soil fertility also increase towards the east. The edaphic changes are paralleled by climatic changes: chiefly a decrease in the severity of summer drought towards the east. On the coast-interior gradient a major non-climatic variable in the gradient is rock cover. High rock cover is a feature of the interior ranges. Soils with organic horizons or with E horizons are a feature on the coastal mountains, but are generally lacking on the interior mountains.